Meta-Analysis of Acupuncture Therapy for Blood Pressure Reduction in Pre-Elderly with Hypertension - Prabowo, Danang Aji; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2024)
Background: Blood pressure tends to increase with age. Hypertension or high blood pressure often occurs in pre-elderly individuals, who are aged between 45-59 years. Acupuncture is one of the therapies with mild side effects that can reduce blood pressure in pre-elderly individuals. This study aims to evaluate the effectiveness of acupuncture therapy in lowering blood pressure in pre-elderly individuals with hypertension based on similar previous research.Subjects and Methods: This study employed a systematic review and meta-analysis based on PICO framework: Population: Pre-elderly individuals with hypertension. Intervention: Acupunc-ture therapy. Comparison: Non-acupuncture therapy. Outcome: Blood pressure. Data were obtained from the PubMed, MEDLINE, Science Direct, BMC, and Google Scholar databases. The search process utilized keywords such as "acupuncture", "hypertension", "Pre elderly", "acupunc-ture for hypertension", AND "acupuncture for blood pressure". Article selection was performed using the PRISMA flowchart, and the results were analyzed using Review Manager 5.3 software.Results: A total of 9 articles originating from the United States, Germany, South Korea, China, India, and Taiwan, with a sample size of 492 subjects, indicated that acupuncture therapy for blood pressure reduction in pre-elderly individuals was not significant for systolic blood pressure (SMD= -0.00; 95% CI= -0.81 to 0.81; p=1.00), but it was significant for diastolic blood pressure (SMD= -1.33; 95% CI= -2.60 to -0.05; p= 0.04).Conclusion: Acupuncture therapy for blood pressure reduction in pre-elderly individuals is not significant for systolic blood pressure, but it is significant for diastolic blood pressure. Keywords: acupuncture, hypertension, pre-elderly, blood pressure, meta-analysis